Exploring Changes in Student Engagement through the RULER Approach: An Examination of Students at Risk of Academic Failure. Issue 1 (2nd January 2019) - Cipriano, Christina; Barnes, Tia N.; Rivers, Susan E.; Brackett, Marc
Abstract: The present paper examines if developmental pathways for students at risk for academic failure can be improved through social and emotional learning (SEL). Specifically, we test this hypothesis by accounting for shifts in student engagement, a highly studied and malleable construct often inclusive of SEL interventions, as the pathway by which to impact student achievement outcomes. Using longitudinal data from a randomized control trial, we identified students at risk for school failure (n = 318) within a larger sample of fifth graders (N = 1, 352). Multigroup path model revealed that participation in RULER significantly impacted the relationship between student engagement and conduct behaviors for at risk students: students who experienced RULER demonstrated increased engagement a year later (at sixth grade) and improved conduct the following year (in seventh grade). The potential for and limitations of SEL programs on developmental trajectories for students at risk for school failure are discussed.